Effect of Cnidoscolous aconitifolius (miller) i.m. Johnston leaf extract on sperm characteristics and reproductive hormones of male rats - Kolapo O Adeleke,; Titi Sangoyomi,; Jones Olanrewaju Moody, (International Journal of Phytomedicine, 2016)
The increase in population growth rate has prompted urgent need to search for plants with antifertility potentials. The present study is concerned with the evaluation of the effect of Cnidoscolous aconitifolius leaf ethanolic extract (LF) on sperm indices and reproductive hormones in male wistar rats. Eighteen male albino rats were divided into three groups (A,B,C) of six animals each. Group A (control) received distilled water while groups B and C received 250 and 500 mgkg-1 leaf extracts respectively on daily basis for fourteen days. Solvent partitioned fractions (n-hexane, dichloromethane, ethyl acetate and aqueous methanol) of the leaf crude ethanol extract were similarly evaluated using another twenty five male rats divided into groups of five. Cotton seed oil (5ml/kg) was used as reference standard Results showed that administration of the extract produced significant decrease (p < 0.05) in sperm count and weight of testis even though there was no significant difference in hormonal level between the treated animals and the control group The reduction in sperm count by C. aconitifolius leaf is an indication of adverse effect on spermatogenesis and provides some justification for further exploitation of this plant as potential male contraceptive.